SARAWAK RUNNERS NETWORK PORTAL - AISHAH, BAKHTIAR (Universiti Malaysia Sarawak (UNIMAS), 2020)
Running event let the runners to experience the ‘intimate’ friendly events while provided with the encouragement and support needed. At the same time, the runners manage to gain a healthy lifestyle, strong mentality endurance and good in time management from joining the running event. There are five types of running events such as trail racing, thriathlons, fun runs, team obstacle racing and ultra racing. But mostly the running events held in Sarawak can only being found through social media which made this hard to let the society recognize the running event. Some runner found it hard to get updated with the running event news and missing the running event's date to book. There is not yet a running event system for Sarawak's state only. To overcome this problem, a Sarawak Runners Network Portal being proposed to ease the runner in Sarawak. The project will be using web-based programming language including HTML, JavaScript and PHP. Rapid Application Development ( RAD ) Methodology has being used along the process of completing this project.